Evaluation of Pharmacognostical Markers Phytochemical Profile and In Vitro Bioactivities of Huberantha Senjiana Leaves (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Huberantha senjiana (Annonaceae), commonly known as the false Ashoka tree, is a medicinal plant distributed in the forest regions of Tamil Nadu. The present study was undertaken to evaluate the pharmacognostical markers, phytochemical profile and in vitro bioactivities of Huberantha senjiana leaves. Fresh leaves were collected from Gingee Hills, Tamil Nadu, authenticated and subjected to detailed macroscopic, microscopic and powder microscopic evaluation. Characteristic diagnostic features such as epidermal cells, stomata, fibres and calcium oxalate crystals were observed and documented. Quantitative pharmacognostical parameters including stomatal number, stomatal index, vein-islet number, vein termination number and palisade ratio were determined using standard procedures. Physicochemical parameters such as total ash, acid-insoluble ash, water-soluble ash, loss on drying, extractive values, swelling index and foaming index were also evaluated to establish quality standards for the crude drug. Successive solvent extracts of the leaves were subjected to preliminary phytochemical screening, which revealed the presence of alkaloids, flavonoids, tannins, phenolic compounds, saponins, steroids and triterpenoids. The hydroalcoholic extract was further evaluated for in vitro bioactivities using suitable experimental methods. The findings of the study provide valuable pharmacognostical standards for the identification and quality control of Huberantha senjiana leaves and demonstrate that the plant possesses diverse bioactive phytoconstituents with promising biological potential, supporting its further investigation for herbal drug development and pharmaceutical applications.
Keywords: Huberantha senjiana; Quantitative pharmacognostical parameters; standards